Study of NF-κB Gene Promoter Region {rs28362691 (-94 ins/del ATTG)} Polymorphism in Patients with Bipolar Disorder: A Case-control Study - Pragyan P Das; Pratima K Sahu; Pratikhya Sarangi; Mihir Ranjan Nayak; Roma Rattan; Saffalya Nayak (Journal of Clinical and Diagnostic Research)
Introduction: Bipolar Disorder (BD), a multifactorial disorder, is associated with increased proinflammatory cytokines due to chronic low-grade inflammation. It affects a relatively younger population. A transcription factor, Nuclear Factor Kappa-B (NF-κB) has an essential role in regulating the cascade of inflammatory responses to psychological stress that occurs in BD. Polymorphism of its promoter region has been a matter of discussion in recent years in schizophrenia but rarely any study has been done in BD. Aim: To evaluate the NF-κB promoter gene polymorphism in healthy subjects and in both types of BD patients, those with mania, and those with depression. Materials and Methods: The current case-control study was conducted at the Department of Biochemistry, SCB Medical College, Cuttack, Orissa, India from March 2020 to February 2022. Individuals aged 18-30 years with BD were included in the study group and age-matched healthy individuals in the control group. A total of 100 cases of newly diagnosed BD (61 BD patients with depressive phase and 39 BD patients with manic phase) and 100 controls were included in the study. Demographic variables such as age and Body Mass Index (BMI) were recorded. A sample of blood was collected from all the participants for genotyping of BD patients. DNA was extracted from Ethylene Diamine Tetraacetic Acid (EDTA) blood and NF-κB gene polymorphism was seen by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method in gel electrophoresis. The quantitative statistical analysis was conducted using SPSS. A p-value of ≤0.05 was considered statistically significant. Results: The common genotype found was del/del in patient groups. Among patients of depression, 32 out of 61 (52.46%) had del/del allele. Similarly in mania patients, 23 out of 39 (58.97%) had del/del allele. The odds of individuals developing BD with depression were the highest in the del/del {9.93 (4.36-22.4)} group. The odds of developing BD with mania were higher in the del/del group {12.94 (5.19-32.24)} than that in the ins/ins group {0.09 (0.04-0.23)}. The del/del type of genotype is higher in mild, moderate, and severe forms of depression as compared to ins/ins and ins/del. Conclusion: The presence of deletion allele in both phases of BD could throw some light on its pathophysiology in neuroinflammation. The findings of the study could lend scope to early genetic screening based on factors including family history to predict the course of BD based on the polymorphisms. This will help strategise the management and genetic counselling approach.